The N2O analogy in the CO2 capture context: Literature review and thermodynamic modelling considerations. (14th April 2015) - Monteiro, Juliana G.M.-S.; Svendsen, Hallvard F.
Abstract: The literature review presented in this work shows that, despite the central role of the N2 O analogy, there is no sound evidence in literature that the ratios of the solubility of N2 O to that of CO2 in water can be used for correlating the solubilities of the two gases in the systems of industrial interest for post combustion CO2 capture, for instance 5 M MEA. On the contrary, the data evaluated in this work indicates that the use of the ratio of the solubility of N2 O to that of CO2 in water may be restricted to systems that are much more dilute than that. The use of the ratio requires that good correlations for Henry's constants of CO2 and N2 O in water are available. However, we show there is a remarkable lack of VLE data on the N2 O–water system in literature. A thermodynamic modelling of Henry's constants of CO2 and N2 O in water is conducted, and two alternative correlations are provided: one for operations up to 1 MPa (typical of post-combustion CO2 capture), and the other for operations up to 20 MPa (for natural gas sweeting process). The correlations for the ratio of the solubility of N2 O to that of CO2 in water are presented together with their 95% confidence bands. Highlights: The N2 O analogy plays a central role in modelling CO2 capture systems. A literature review of the solubility of CO2 and N2 O in water is presented. Thermodynamic modelling of the solubility of CO2 and N2 O in water is presented. New correlations for the N2 O analogy are proposed.